Ecvet as a vehicle for better mobility? Moving from recommendation to practice : experiences and results gained from the pilot projects SME Master Plus, AEROVET, CREDCHEM unf VaLOGReg (2009-2012) - Eberhardt, Christiane [Herausgeber]; Esser, Friedrich Hubert [Mitarbeiter]; Thomann, Birgit [Mitarbeiter]; Born, Volker [Mitarbeiter]; Sperle, Christian [Mitarbeiter]; Saniter, Andreas [Mitarbeiter]; Schlegel, Beatrice [Mitarbeiter]; Berg, Hans-Jürgen [Mitarbeiter]; Küßner, Karin [Mitarbeiter]; Luomi-Messerer, Karin [Mitarbeiter] (Bundesinstitut für Berufsbildung, 2012)
"The Copenhagen Declaration of 2002 initiated a multitude of activities aimed at fostering the mobility of individual persons and at increasing the transparency of qualifications. One of these initiatives encompasses the development of the European Credit System for Vocational Education and Training, or ECVET. The aim of ECVET is to establish a procedure which permits the transfer and reciprocal recognition of learning outcomes achieved in different educational systems and within various contexts of initial and continuing vocational education and training. One major stage of development is marked by the 'Proposal for the establishment of a European Credit System for Vocational Education and Training (ECVET)', which was adopted by the European Parliament in December 2008. Following a test phase suggested by a majority of the member states, the European Commission published an open call for tenders on the 'Testing and Development of the European Credit System for Vocational Education and Training - ECVET in May 2008. Eleven projects were selected to pilot ECVET across the whole of Europe during the period from 2009 to 2012. The present publication 'ECVET as a vehicle for better mobility? From the European Recommendation to piloting in practice' adresses the experiences and results gained from the pilot projects SME Master Plus, AEROVET, CREDCHEM and VaLOGReg with the objective of debating the opportunities for and limitations of applying ECVET within the context of the promotion of European mobility with representatives from practice and policymaking." (BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; G 1.3.3.3 Mobilität; Europäisches Leistungspunktesystem; Berufsbildung; Berufliche Mobilität